Investigation on maneuverability improvement of a four-wheel drive and rear-wheel steering system : numerical simulation analysis - Li, Maoqi (2023)
X-by-wire technology is an advancement in the automotive industry and is recognized by many countries in recent years. It includes drive-by-wire (DBW) and steer-by-wire (SBW). DBW is available in two-wheel drive (2WD) and four-wheel drive (4WD) forms. 4WD has two forms: centralized motor drive and distributed motor drive. A centralized motor drive is to use the motor to replace the engine to provide power for the vehicle. The distributed motor drive is mainly based on the in-wheel motor, and the wheel is driven by the in-wheel motor to provide power for the vehicle. SBW has two forms: two-wheel steering (2WS) and four-wheel steering (4WS). It not only dramatically reduces the operating burden of the driver but also solves the problem that ordinary vehicles cannot perform 4WS. Usually, the lower maneuverability is easy to show on 2WS vehicles during vehicle turning. No matter when driving a vehicle on a narrow city road or parking, it is required to turn the steering wheel several times when the vehicle needs to steer. Moreover, the vehicle can be prone to understeer (US) or oversteer (OS) phenomena that occur when steering. The main purpose of this research is to simulate the steering performance of the vehicle by constructing a model of modern conventional vehicles and to solve the problems that may occur during vehicle cornering by applying an active 4WS control system to control the yaw rate. In this research, experiments of 2WS cornering at several constant speeds and steer angles were conducted using an actual experimental vehicle. A simulation model of the test car was constructed in MATLAB Simulink using nonlinear vehicle dynamics equations with the specification of the vehicle as the parameters. A PID control system was used in this simulation to control the rear-wheel steering angle in order to achieve 4WS. By comparing the simulation and the experimental result, it can be concluded that the nonlinear vehicle dynamics equation can be used to do the simulation of the vehicle motion. After verifying the vehicle dynamics equation, in order to verify whether the time of rotating the steering wheel will affect the motion of the vehicle, this study simulated two different times to complete the rotation of the wheel which is 2 seconds and 25 seconds with the front steering angle is 10 degrees. The results show that no matter whether the time of steering wheel rotation is fast or slow, it does not affect the speed of the vehicle's US and OS phenomenon. By simulating the cornering situation of the vehicle speeds from 10km/h to 80 km/h in the 10km/h increment. It is concluded that the vehicle will occur US phenomenon when the vehicle turning speed is lower around 20km/h; when the vehicle corners with a speed higher than 50km/h, the vehicle will have an OS phenomenon happen. After applying the 4WS system, the OS and US problems are solved efficiently. Although the vehicle is turning at a speed of 80km/h, steady-state cornering (SSC) can still be achieved. After applying the PID control system, most of the cornering can be controlled. except when the wheels rotate to 10° in only two seconds and the vehicle speed is greater than 60km/h which is the vehicle is out of control in a very short time, the PID control system cannot make the rear wheels have an appropriate steering angle to make the vehicle have an SSC. In short, this study solved almost all US and OS phenomena that can occur in 2WS vehicles by applying the 4WS system.